2022
DOI: 10.1038/s41467-022-28276-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations with carotid intima-media thickness link to atherosclerosis with sex-specific effects in sub-Saharan Africans

Abstract: Atherosclerosis precedes the onset of clinical manifestations of cardiovascular diseases (CVDs). We used carotid intima-media thickness (cIMT) to investigate genetic susceptibility to atherosclerosis in 7894 unrelated adults (3963 women, 3931 men; 40 to 60 years) resident in four sub-Saharan African countries. cIMT was measured by ultrasound and genotyping was performed on the H3Africa SNP Array. Two new African-specific genome-wide significant loci for mean-max cIMT, SIRPA (p = 4.7E-08), and FBXL17 (p = 2.5E-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…This study included younger patients compared to our study, where all patients were 40 years and older; this explains why our prevalence of CA is higher than theirs. In addition, the variation in prevalence could also be explained by the genetic diversity of the African populations, where genetic associations with CIMT and its link to atherosclerosis with sexspeci c effects have been proven, especially in sub-Saharan Africans [29]. This meta-analysis, however, did not evaluate the effect of non-HDL-c/HDL-c on the CIMT, nor had it determined the predictors of CA.…”
Section: Discussionmentioning
confidence: 95%
“…This study included younger patients compared to our study, where all patients were 40 years and older; this explains why our prevalence of CA is higher than theirs. In addition, the variation in prevalence could also be explained by the genetic diversity of the African populations, where genetic associations with CIMT and its link to atherosclerosis with sexspeci c effects have been proven, especially in sub-Saharan Africans [29]. This meta-analysis, however, did not evaluate the effect of non-HDL-c/HDL-c on the CIMT, nor had it determined the predictors of CA.…”
Section: Discussionmentioning
confidence: 95%
“… 28 Sex‐specific genetic effects were also considered. 29 Nevertheless, postmenopausal hormone replacement therapy was not proved to ultimately reduce the risk of atherosclerosis, which indicates biological mechanism of female hormones still needs to be further studied. 30 Iemolo et al found that sex hormones may influence the remodeling of atherosclerosis, causing more stenosis but less plaque presence in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that estrogen could optimize metabolism, macrophage or smooth muscle cell function, which help women to resist atherosclerosis 28 . Sex‐specific genetic effects were also considered 29 . Nevertheless, postmenopausal hormone replacement therapy was not proved to ultimately reduce the risk of atherosclerosis, which indicates biological mechanism of female hormones still needs to be further studied 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Testing association is a crucial part of GWAS as the positive genes are reported from this inferential procedure in a case-control study design. The contingency table tests for individual single-nucleotide polymorphism (SNP) are carried out here, where, the individual genotype counts are handled with the phenotype (case-control) [3] [5] [6] [9] [10] [11] [12]. Generally, the two degrees of freedom (d.f.)…”
Section: Introductionmentioning
confidence: 99%